Antibiotic prophylaxis for oral lacerations: our emergency department’s experience - Katsetos, Suzanne Lilley (Int J Emerg Med, 2016)
BACKGROUND: The purpose of this study was to examine the emergency physician (EP) practice of prescribing prophylactic antibiotics for patients with oral lacerations. A secondary outcome measure was the infection rate of those who were or were not prescribed antibiotics. METHODS: The study was a retrospective chart review of 323 patients who presented to a large urban emergency department (ED) between January 1, 2012 and December 31, 2012 with an oral laceration. RESULTS: Of the 323 charts reviewed, topical and/or systemic antibiotics were prescribed in the ED to 62 % (199/323) of patients. Of those patients, 38 % (75/199) received only topical antibiotics, 34 % (68/199) received only systemic antibiotics, and 28 % (56/199) were prescribed topical and systemic antibiotics. Thirty-eight percent (124/323) of patients received no antibiotics. Eighteen percent (58/323) of patients returned for follow-up with an infection rate of 10 % (6/58). There was a statistical difference in rates of infection between patients who received antibiotics and who did not receive antibiotics and a statistical difference in rates of infection between patients with complex lacerations who received and did not receive antibiotic. CONCLUSIONS: This study shows that there is a considerable amount of practice variance in prescribing prophylactic antibiotics for oral lacerations among EPs in our ED. Due to the poor follow-up rate, an accurate infection rate could not be determined. In the future, adequately powered randomized controlled studies may provide compelling data for or against the necessity for prophylactic antibiotic use for oral lacerations.